Sustainable ruminant production to help feed the planet. Issue 1 (2nd January 2017) - Pulina, Giuseppe; Francesconi, Ana Helena Dias; Stefanon, Bruno; Sevi, Agostino; Calamari, Luigi; Lacetera, Nicola; Dell'Orto, Vittorio; Pilla, Fabio; Ajmone Marsan, Paolo; Mele, Marcello; Rossi, Filippo; Bertoni, Giuseppe; et al.
Abstract: Ruminant production has been an essential part of human activities worldwide since ancient times. The expected increase in world population and per capita income, with an increase in the amount and prevalence of animal products in human diet, urbanisation, with a concentration of population in urban areas and an increase in losses in the supply chain, and the growing concern over the environmental impact of animal farming require a long-term global strategy for a more intensive and sustainable ruminant production. Therefore, solutions to increase the supply of high-quality products of ruminant origin, without harming human health, animal welfare, and environment, should consider the following interconnected issues discussed in this review: (a) effects of meat, milk and dairy products consumption on human health, focussing on the imbalance caused by their insufficient consumption, and the alleged increased incidence of certain diseases due to their consumption; (b) importance of the sustainable intensification of ruminant production systems (e.g. better feed conversion and higher production output per unit of input introduced into the farming system); (c) environmental impact of ruminant production; (d) improvement of animal performance by improving animal welfare; (e) adaptation of ruminants to climate change; (f) sustainable ruminant feeding (e.g. precision feeding techniques, optimisation of grazing systems, and use of unconventional feeds); (g) challenges posed by production intensification to animal breeding and conservation of animal biodiversity; and (h) strategies to increase ruminant production in developing countries, thus achieving food security in vast areas of the planet affected by fast growth of human population.